Al-Itqan fi Ulum al-Qur'an - Jalaludin Al-Suyuti
Al-Itqan fi `Ulum al-Qur'an (Precision and Mastery in the Sciences of the Qur'an) is perhaps the most outstanding work of its kind in the field of Qur'anic Sciences.Exhaustive in its sources and its subjects, thoughtfully and lucidly written, the work is also well arranged. Readers will be taken by the depth, breadth, scope, and mastery of the author while noting how much Muslim scholars have devoted to the study of the Qur'an and how varied and diverse were the fields in which those studies were made.